How does social support affect functional impairment in late life?: findings of a multicenter prospective cohort study in Germany - Hajek, André; Weyerer, Siegfried (Age & ageing, 2017)
Abstract: Objective: to investigate how social support affects functional impairment (FI) in late life in a longitudinal approach. Methods: in a multicenter prospective cohort study, subjects in old age (≥75 years at baseline) were interviewed every 1.5 years. Social support was quantified in the follow-up (FU) Waves 2 and 4 (FU Wave 2: n = 2,349; FU Wave 4: n = 1,484). FI was assessed by using the Lawton and Brody Instrumental Activities of Daily Living scale. Results: fixed effects regressions showed that a decrease in social support is associated with FI in the total sample and in both sexes. The effect on FI was most pronounced with the dimension social integration, whereas changes in practical support only affected FI in the total sample and changes in emotional support only affected FI in men. Conclusions: our findings emphasise the importance of social support for functional status in late life. Thus, strengthening social support in old age might be effective in maintaining functional abilities.